Life stage and seasonal habitat use of the porbeagle Lamna nasus in the Northwest Atlantic Ocean - Anderson, Brooke N.; Hammerschlag, Neil; Saul, Steven; Dodd, Jon F.; Bowlby, Heather D.; Kang, Yun; Gallagher, Austin J.; Sulikowski, James A. (Frontiers in Marine Science, 2025)
For highly mobile marine species such as pelagic elasmobranchs, the development of effective spatial management requires a comprehensive understanding of movement ecology. Research incorporating movement data across seasons and life stages, including reproductive states, is valuable for informing spatial management, yet is absent for most species. In the Northwest (NW) Atlantic Ocean (hereafter referred to as NW Atlantic), the porbeagle shark Lamna nasus is a pelagic species that is overfished, has a live retention ban (Canada) or landings regulations (United States), and is also commonly captured incidentally as bycatch. Research on the spatiotemporal dynamics of NW Atlantic porbeagle habitat use is limited, with all previous research utilizing pop-off satellite archival tags that are prone to large uncertainty in location estimates. This study used higher-accuracy fin-mount satellite tags to identify patterns in habitat use across life stages and seasons for porbeagle sharks tagged off the northeastern coast of the United States. During the summer and fall, the 95% kernel density estimate (referred to as “activity space”) of tagged porbeagles occurred almost exclusively on the continental shelf in the Gulf of Maine and Georges Bank. Activity space expanded and shifted southwards to include offshore environments during the winter and spring for juveniles, mature non-gravid females, and mature females of unknown reproductive states, while the activity space of mature males and gravid females remained in shelf waters year-round. This finding differs from the previous assumption that southward migrations are linked to reproduction for NW Atlantic porbeagles. Tagged porbeagles were also found to have a relatively small 50% kernel density estimate (referred to as “high occupancy area”) located around Cape Cod, Massachusetts that was well-conserved across life stages and seasons. This relatively static, small high occupancy area has implications for the population’s conservation given the high amount of fishing activity (rod-and-reel, trawl, gillnet) occurring within this region. Given the overlap between porbeagle high occupancy area and fishing activity, as well as the relatively high recapture rate of tagged sharks (10.5%), the coastal waters around Cape Cod, Massachusetts should be considered for spatial management of the NW Atlantic porbeagle.